Ethics of Alaska Travel Writing since 1959 : An Ecocritical Study - Ferguson, Benjamin, (Arctic Humanities ;, 2025)
This book digs into environmental themes in Alaska travel writing since U.S. statehood in 1959, drawing on the works of six authors including Barry Lopez, Jonathan Raban, Tom Lowenstein and others. Each work, though disparate in style, advocates for the empowerment of the Alaska Native people by connecting not only with diverse perspectives but with the lived realities in the geographical spaces that have formed them. In analyzing how these authors have succeeded in depicting the realities of alterities, and where they have perhaps fallen short by more recent standards, we may begin to carve out a system of ethics. This is important as fresh waves of travel writers search for their own place in the environmental conversations surrounding the ever-evolving, 21st century Arctic and its place on the front lines of a changing climate.